Adaptation and removal mechanism of anion chromium and cation cadmium by sulfate-reducing bacteria culture systems under different carbon sources. Issue 2 (April 2023) - Ma, Suya; Zhao, Qiancheng; Du, Yanbin; Hu, Xuesong; Zhang, Jiale; Tan, Huadong; Qiu, Fuyuan; Yu, Caihong
Abstract: A major factor limiting the application of sulfate-reducing bacteria culture systems (SRBs) to the removal of heavy metals is the requirement to supply carbon and energy to drive the process. In this study, the effects of carbon sources on the SRBs under Cr(VI) and Cd(II) domestication conditions were comprehensively investigated, and two dominant groups with humic acid and sodium lactate as carbon sources were selected to study the mechanisms of transformation. Results showed that the order of carbon source utilization was humic acid > sodium lactate > glycerol > mixed carbon sources > glucose. Differences in the rate and extent of utilization of carbon sources resulted in different diversity, structure, and function of SRBs. Differences in carbon sources can lead to an increase or decrease in certain functions, e.g., nitrogen fixation is enhanced in the humic acid group. The fermentative bacteria play a key role in degrading macro-organics to volatile fatty acids, which are then utilized by SRBs to reduce sulfate. For the anion Cr(VI), the SRBs culture system reduced Cr(VI) to Cr(III) mainly through the H2 S pathway; for the cation Cd(II), the EPS pathway, electron transport pathway, and H2 S pathway all had good removal effects. These findings provide a new perspective on strain screening and heavy metal removal. Highlights: The metabolic pathways of carbon sources affect SRBs culture system. The selection of carbon sources is a guideline for strain screening. Revealing the transformation mechanism from microbial metabolism level. Comparison of mechanisms of anion and cation removal by SRBs culture system. Domestication can improve the efficiency of heavy metal removal.